2014
DOI: 10.31989/ffhd.v4i6.9
|View full text |Cite
|
Sign up to set email alerts
|

14C-Psilocin tissue distribution in pregnant rats after intravenous administration

Abstract: Background: Many species of hallucinogenic mushrooms have been found in the genusPsilocybe. The main psychoactive chemicals of Psilocybe mushrooms are psilocin and its phosphoryloxy derivative, psilocybin. In addition to its psychedelic effects, psilocybin is an effective agent to lift the mood of depressed patients with terminal cancers. Objective:To study the dispositional kinetics of 14 C-psilocin in pregnant rats after intravenous injection, to calculate tissue dose surrogates i.e., tissue 14 C concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, the concentrations of active principles may va species, origin, size, age, growing, and drying conditions [26]. In an found that after oral administration, 50% of the 14C-labelled psilocin almost evenly distributed throughout the body, including the brain [ studies, after intravenous administration, the 14C-psilocin crossed t reaching fetal tissue concentrations lower than maternal tissue, but w nation half-life [28]. In adult men, following oral administra dephosphorylated to psilocin from the hydrochloric acid made by t Furthermore, psilocybin is dephosphorylated to psilocin in the int blood by the alkaline phosphatase and nonspecific esterases [29,30].…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the concentrations of active principles may va species, origin, size, age, growing, and drying conditions [26]. In an found that after oral administration, 50% of the 14C-labelled psilocin almost evenly distributed throughout the body, including the brain [ studies, after intravenous administration, the 14C-psilocin crossed t reaching fetal tissue concentrations lower than maternal tissue, but w nation half-life [28]. In adult men, following oral administra dephosphorylated to psilocin from the hydrochloric acid made by t Furthermore, psilocybin is dephosphorylated to psilocin in the int blood by the alkaline phosphatase and nonspecific esterases [29,30].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…In animal studies, it was found that after oral administration, 50% of the 14C-labelled psilocin was absorbed and almost evenly distributed throughout the body, including the brain [ 27 ]. In pregnant rat studies, after intravenous administration, the 14C-psilocin crossed the placental barrier reaching fetal tissue concentrations lower than maternal tissue, but with a slower elimination half-life [ 28 ]. In adult men, following oral administration, psilocybin is dephosphorylated to psilocin from the hydrochloric acid made by the stomach [ 29 , 30 ].…”
Section: Pharmacokineticsmentioning
confidence: 99%